Innovative and Collaborative Governance in The Implementation of Regulation No. 84 of 2017 Sidoarjo - Lussi Agustin; Moh. Yusron Solikin (Iapa Proceedings Conference, 2021)
This research aims to analyze the implementation of Sidoarjo Regency Regent Regulation No. 84 of 2017 on Structuring and Empowerment of Street Vendors based on Innovative and Collaborative Governance theory. The method used in this research is a qualitative method using empirical studies from previous research and regulations related to the Structuring and Empowerment of Street Vendors. Collaborative governance has four stages in the process, namely assessment, initiation, deliberation and implementation. The results of this study show that the Cooperative and Micro Enterprises Office of Sidoarjo Regency has implemented Innovative and Collaborative governance. This is evidenced by the structuring and empowerment of street vendors through how to move Street Vendors to a more viable selling location is one of the breakthroughs of the Sidoarjo Regency Cooperative and SMEs Office. This breakthrough is considered very appropriate to solve the problem of street vendors who sell in the Kludan Sidoarjo tourist market area which in the buying and selling process interferes with the interests of pedestrians on the sidewalk. Then with the new selling place street vendors will be more centralized and can increase their sales.